The Effect of Chitosan Concentration on the Mechanical Strength of Anti- Bacterial Biodegradable Plastic Made from White Sweet Potato Starch (Ipomoea batatas) - Lia Mairiza; Sofyana Sofyana; Aula Chairunnisak; Putri Syafrilia; Silvera Isnaini (Journal of Applied Technology, 2023)
Research on antibacterial biodegradable plastic made from white sweet potato starch (Ipomoea batatas) has been carried out. The purpose of this study was to examine the effect of chitosan concentration on mechanical strength. The independent variables used were the concentration of chitosan, which was 0%; 0.01%; 0.03%; 0.05%; 0.07% (w/v). The mechanism of this research was carried out by dissolving various concentrations of chitosan in glacial acetic acid, with a concentration of 10% (w/v) white sweet potato starch dissolved in distilled water, then adding glycerol as a plasticizer at a gelatinization temperature between 80o-95oC, using a stirring speed of 75 rpm. The research results show that the addition of chitosan can increase the tensile strength value of the film mixed with chitosan and sweet potato starch, where the maximum tensile strength value obtained in this study is found in films with a concentration of 0.07% chitosan worth 0.0645 kgf/cm2 and a maximum value of % elongation of the starch mixture film white sweet potato and chitosan were obtained from films with a chitosan concentration of 0.07%, which is around 5.6%. Meanwhile, the white sweet potato plastic film without chitosan had tensile strength and elongation values of 0.0577 kgf/cm2 and 10.7%, respectively.